Hydromechanical modelling of CO2 sequestration using a component-based multiphysics code. Issue 1 (15th September 2019) - Chen, Qiushi; Lai, Zhengshou
Abstract : Geologic carbon dioxide sequestration (GCS) is a complex process with coupled multiphysics mechanisms, including non-linear solid deformations and fluid flow. When applying a finite-element method to solve such a complex problem, implementing and solving non-linear partial differential equations with sophisticated material models pose great challenges. In this work, a generic component-based multiphysics analysis code – Albany – is introduced for the modelling and analysis of GCS problems. The component-based approach allows the application code development effort to focus on writing physics models. A notable feature of Albany is the powerful automatic differentiation utilities that can be used to calculate automatically system Jacobians and consistent tangents. Two numerical problems, namely, wellbore injection and carbon dioxide transport in a confined underground channel, are developed to demonstrate the performance of the Albany analysis framework. The results are verified against and matched well with those from Comsol – a robust commercial multiphysics finite-element package. The numerical results are also thoroughly analysed to gain insights into distribution profiles and temporal evolutions of pore pressure and displacement fields during a GCS process.